Espaço cultural, espaço público: estudo sobre as políticas culturais brasileiras e as relações de poder nos espaços Lagoa do Nado, Centro Cultural UFMG e Palácio das Artes - Hely Rodrigues Vieira de Souza (2012)
The formation of creative and critical citizens is closely linked to the right to culture and to the city, with its integration spaces. Understanding culture as a plural reality allows the understanding that cultural diversity is its main power. Thus, the processes of cultural homogenization, since they are processes of alienation, as pointed by Lefebvre, and of isolation of individuals, according to Arendt, can also deconstruct the emotionalties built by Culture. After all, at the same time that culture has a plurality in its essence, it also forms links, affiliations and collective identities. Therefore, the right to culture would be entitled to be part of this diversity, and also to enjoy it. Culture as a right is a possibility to profoundly open democratic participation in Brazil and to achieve a just and pluralistic society that respects the diversity that culture provides, in the design andconstruction of public spaces. The cultural public spaces and cultural public policies could operate, by excellence, as a mechanism to guarantee the quality training, especially for young people. To make this training possible, it is necessary to study the meanings of the expressions public space and cultural space, in a deepen discussion. InBelo Horizonte city there are three important areas that have the making for the implementation of this study (theoretical, reflective and practical study, with interviews and field work), which are: Palácio das Artes, Centro Cultural Lagoa do Nado and Centro Cultural UFMG. The study of these spaces can be linked to power relations, to cultural public policies, to politics, to economy, to the interests of the State and civil society. Thus, it is also possible to link theory to practice in the pursuit of understandingthe public space, embodied in the form of cultural space.